THE IMPACT OF THE MARKET CYCLE ON THE VALUE RELEVANCE OF BOOK VALUES AND EARNINGS IN THE BANKING INDUSTRY: AN EVIDENCE FROM POLAND - P. M. Bolibok (Финансы: теория и практика, 2018)
The paper aims at the empirical investigation of the impact of the market cycle on the value relevance of book values and earnings in the banking industry. unlike most prior studies, the paper directly examines the influence of cyclical fluctuations in investors’ sentiments on the informativeness of these key accounting variables. Moreover, the study enhances the literature on the value relevance of banks’ financial reporting by providing an empirical evidence from the emerging capital market ofPoland. The examined sample covers all domestically-based commercial banks listed on the Warsaw Stock Exchange over the period 1997–2016. The empirical evidence based on the analyses of parametric and non-parametric correlation and regression indicates a significant impact of the market cycle on the value relevance of book values which markedly increases (decreases) in the periods of bull (bear) market. In contrast, the informativeness of earnings seems to be driven primarily by factors other than investors’ sentiments. The results of the research indicate that the course of the market cycle is partially driving the fluctuations of the value relevance of book values of equity and net earnings in the Polish banking industry. There is a need for further investigation of the impact of market cycles on the value relevance of accounting data, not only in the context of the banking sector.